On the evolution of the model of shifting mode of reproduction - V. I. Maevsky; S. Yu. Malkov; A. A. Rubinstein (Russian Journal of Economics and Law)
Objective: to analyze the evolution of shifting mode of reproduction (SMR) models, to construct the SMR-3 model. Methods: abstract-logical method, methods of modelling the economic dynamics in relation to the switching regime of reproduction of fixed capital.Results: despite the fact that fixed capital is necessarily taken into account both in reproduction schemes and in models of economic growth, the peculiarities of economy functioning arising from the coexistence of different generations of fixed capital have remained outside both the economic mainstream and heterodox studies. The article briefly describes the theory of switching reproduction regime (SMR), which fills this gap. Several types of SMR models (SMR-1, SMR-2, SMR-3) are considered, which differ from each other in the degree of the monetary mechanism development that serves the reproduction processes occurring in the real sector of the economy. By the example of determining the degree of influence of the fixed capital investments structure on the key macro indicators in the Russian Federation, the possibilities of the most advanced SMR-3 model are demonstrated. On this basis, the scenario was simulated of the Russian economy transition from the typical for 2014 financing structure (46 % - own funds, 30 % - funds of budget and higher organizations, 24 % - other borrowed funds (loans)) to the new structure, where own funds are equal to 50%, funds of budget and higher organizations - 20 %, other borrowed funds - 30 %. It is established that this transition contributes to the growth of profitability and GDP. Scientific novelty: the model SMR-3 is constructed, which allows to take into account the functioning of the banking system and the budget mechanism, based on the effect of ergodicity and the fact that the funds coming from all subsystems to the updated subsystem are not only credit resources, but also the so-called intra-company funds flowing into the updated subsystem at no cost.Practical significance: it is shown that the SMR-3 model can be used to carry out practical calculations for various scenarios of socio-economic development.